Family Firms and Economic Development - Surdej, Aleksander (Firmy rodzinne w rozwoju gospodarczym, 2010)
The article discusses the relationship between the density of family firms and the economic development. The author shows that families are universally one of supporting factors of the creation of new businesses by supplying necessary capital, work or moral support. But families may become an obstacle to the growth of companies once they expand and need to change ownership or organizational forms. Thus, families may face a dilemma between orientation towards growth and willingness to maintain the control over the company. How and with what consequences for economic development this dilemma is solved depends on the institutional environment characterizing the economy. The second part of the article identifies mechanisms, which relate to the growth dynamics of family firms to selected institutional factors.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 113, s. 905-926
Keywords: family firms; ownership and control succession; succession strategies; institutional environment institutions; economic development